Education Quality Management in Improving User Services at Madrasah Ibtidaiyyah Miftahul Jannah Sekampung, East Lampung, Lampung - Tukiran (Program Studi Manajemen Pendidikan Islam, Fakultas Tarbiyah, Institut Pesantren Sunan Drajat Lamongan, 2023)
The quality of education can be seen from the management in every institution or institution, especially in schools or madrasas. Departing from how the quality of education in a school or madrasa seen from the service users who in the future can improve the quality of education.This research is included in the field qualitative research. Data collection techniques used are: interview method, observation method and documentation method. The data analysis technique used is qualitative analysis. The process of qualitative data analysis according to Mathew B. Miles and A. Michael Huberman, through the process of data reduction, display (presentation of data) and verification. The results showed that madrasah ibtidayyah miftahul janah had a good quality of education which could be seen in school management in improving the quality of users which consisted of four aspects including; 1) Aspects of Physical Evidence (tangibles), 2) Aspects of Empathy, 3) Aspects of Reliability, and 4) Aspects of Responsiveness.